Inter-industry analyses among micro, small, medium and large enterprises in Malaysia - Utit, Chakrin (2021)
This thesis is motivated from the view of economic unbalanced between production sizes and economic contribution of micro, small and medium enterprises (MSMEs) in the Malaysian economy. Specifically, it deals with the analyses of the structural differences between MSMEs and large firms in explaining the unbalanced economic contribution. The structural differences are measured by focusing on three different issues. First, it addresses how differences in production structures between MSMEs and large firms contribute to the variations in multiplier impacts. Second, it further details the analysis of differences in production structures by measuring the extent to which the resource-based Government-Linked Companies (GLCs) have influenced the unbalanced contribution of MSMEs. Third, it examines the extent to which the different production structures affect the level of income distribution at different household groups. The three issues are analysed by using two new and novel databases, the so-called MSME-Input-Output (MSME-IO) Table and MSME-Social Accounting Matrix (MSME-SAM), which are specifically developed for this study. The first and second issues are analysed by applying the MSME-IO while MSME-SAM is used to address the third issue. Three key findings are drawn from this study. First, one-size fits all measures is bias as the use of only the proportionality approach to estimate the economic impacts of production sectors tends to overestimate the economic benefits of MSMEs. Second, resource-based GLCs are found to associate with less economic spill over to MSMEs. Third, smaller production sizes, particularly the micro and small-sized sectors contribute relatively higher income multipliers. Altogether, analyses have validated the superiority of utilising disaggregated databases for policy analyses of MSMEs. Based on the superiority of the databases, four key recommendations and policy reflections to improve the future contributions of MSMEs are provided. They include the importance of having updated and regular inter-industry databases for progress monitoring, strengthening of existing linkages programmes, establishing MSMEs content requirement policy, and strengthening digitalisation among MSMEs for productivity improvement.